2022
DOI: 10.1021/acs.jpcc.1c08914
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Phase Drives the Assembly of Gold Nanoparticles on Biomimetic Lipid Bilayers

Abstract: In recent years, many efforts have been devoted to investigating the interaction of nanoparticles (NPs) with lipid biomimetic interfaces, both from a fundamental perspective aimed at understanding relevant phenomena occurring at the nanobio interface and from an application standpoint for the design of novel lipid–nanoparticle hybrid materials. In this area, recent reports have revealed that citrate-capped gold nanoparticles (AuNPs) spontaneously associate with synthetic phospholipid liposomes and, in some cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…Figure 6A and 6B). Coarse-grained simulations of citrate-capped AuNPs with freefloating DPPC membranes 82 suggest that for absorption to occur on a DPPC SLB, a substantial portion of the membrane would need to be lifted off the mica to expose the lipid tails to the AuNP, which would be highly energetically unfavorable in a SLB system.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6A and 6B). Coarse-grained simulations of citrate-capped AuNPs with freefloating DPPC membranes 82 suggest that for absorption to occur on a DPPC SLB, a substantial portion of the membrane would need to be lifted off the mica to expose the lipid tails to the AuNP, which would be highly energetically unfavorable in a SLB system.…”
Section: Resultsmentioning
confidence: 99%
“…Berti and our group revealed that the lipid fluidity helped the self-assembly of cit-Au onto the liposomal membrane. 37,40 On the basis of these studies, we reason that the low viscosity of the surrounding fluidphase lipids allows faster diffusion of Au@Pt/Lipid complex. In addition, because of the identical surface ligand of cit-Au and Au@Pt, 47 the citrate−lipid ligand exchange at the interface may lead to Au@Pt aggregation on the fluid-phase liposomes.…”
Section: Resultsmentioning
confidence: 97%
“…We reason that the dynamic organization of catalytic NPs may also be effective. , A fluid liposomal surface may provide an attractive platform to test this hypothesis. , Moreover, understanding the interaction between NPs and phospholipid membranes impacts the development of biophysics, medicine, plant science, and nanobiotechnology. A lot of simulation and experimental work have revealed the effect of particle types, size, charge, shape, and surface chemistry on the interaction with phospholipid membranes. Nevertheless, to the best of our knowledge, although individual nanoparticles associating with each other spontaneously into a defined and organized structure has been widely explored, manipulating the assembly of NPs on lipid membranes is still challenging. Previous studies reported that fluid-phase liposomes could promote the aggregation of citrate-capped gold NPs (cit-Au), providing another way to manipulate NP assembly on fluid-phase lipid surfaces. Ma et al controlled the assembly of cit-Au on fluid-phase liposomes, providing a practical approach for deep tissue immunogenic cell death cancer immunotherapy with hybrids’ near-infrared II optical absorption property …”
Section: Introductionmentioning
confidence: 99%
“…Since the optical properties of metallic particles are connected to the interparticle distance, the optical variations in the absorbance of metallic NPs can be used to monitor their aggregation. Generally, such aggregation provokes the broadening of the plasmonic peak, the red shift of its maximum, and even the occurrence of a new red-shifted peak depending on the morphology of the aggregates ( Cardellini et al, 2022 ). All these variations, easily monitorable through UV-Vis Spectroscopy, represent an excellent tool to determine the interaction of NPs with their environment in biomimetic studies, colorimetric assays, and biosensing applications, as we recently presented in different studies.…”
Section: Resultsmentioning
confidence: 99%
“…In recent works, a combination of computational and experimental results highlighted that the spontaneous aggregation of citrated AuNPs on vesicles of lamellar nature is triggered by the fast release of citrate anions at the AuNPs surface ( Montis et al, 2020b ; Salassi et al, 2021 ; Cardellini et al, 2022 ). Such release occurs upon adhesion of AuNPs to the vesicles’ membrane, which drives the displacement of citrate anions by the lipids composing the vesicles’ membrane (i.e., a citrate/lipid ligand exchange).…”
Section: Discussionmentioning
confidence: 99%